THE UTILISATION OF INDUSTRIAL PROCESS MODELS IN ACQUIRING THE PRACTICAL SKILLS OF PLC PROGRAMMING - Jakubiec, Beata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the paper the use of process models and computer simulation as the tools which facilitates students to learn the conditions of the industrial processes control has been presented. Such approach enables to familiarise with operation and programming of controllers of industrial process. Moreover, it also enables safe testing of control algorithms provided by logic controllers through their implementation at the real industrial facility.